Novel Paired Cell Lines for the Study of Lipid Metabolism and Cancer Stemness of Hepatocellular Carcinoma - Cheng, Yun-Hsin; Ko, Ying-Chieh; Ku, Hsiang-Ju; Huang, Ching-Chun; Yao, Yu-Ching; Liao, Yi-Tzu; Chen, Ying-Tsong; Huang, Shiu-Feng; Huang, Li-Rung (Frontiers in Cell and Developmental Biology, 2022)
There are few well-characterized syngeneic murine models for hepatocellular carcinoma (HCC), which limits immunological studies and the development of immunotherapies for HCC. We previously established an oncogene-induced spontaneous HCC mouse model based on transposon-mediated oncogene (AKT and NRASV12) insertion into the genome of hepatocytes to induce tumorigenesis. Two tumor clones with different levels of lipid droplets (LDs) showed similar in vitro growth but distinctive in vivo phenotypes, including divergent proliferative capability and varying induction of myeloid-derived suppressor cells (MDSCs). The two clones showed distinct gene expression related to lipid metabolism, glycolysis, and cancer stemness. Endogenous fatty acid (FA) synthesis and exogenous monounsaturated fatty acid (MUFA) consumption promoted both tumor proliferation and cancer stemness, and upregulated c-Myc in the HCC cell lines. Moreover, the LDhi HCC cell line expressed a higher level of type II IL-4 receptor, which promoted tumor proliferation through binding IL-4 or IL-13. The chromosomal DNA of two tumor clones, NHRI-8-B4 (LDhi) and NHRI-1-E4 (LDlo) showed five identical AKT insertion sites in chromosomes 9, 10, 13, 16 and 18 and two NRAS integration sites in chromosomes 2 and 3. Herein, we describe two novel HCC cell lines with distinct features of lipid metabolism related to cancer stemness and differential interplay with the immune system, and present this syngeneic HCC mouse model as a practical tool for the study of cancer stemness and discovery of new therapies targeting liver cancers.